New Epoxy End-Functional Polystyrene Synthesized by Atom Transfer Radical Polymerization - HASAN, TARIQUL; KUMAR SARKER, ASHIS (Asian Journal of Chemistry, 2010)
A new initiator undecenyl-2-bromopropionate (UBP) was synthesized and it was successfully applied for CuBr-bipyridine (Bipy) mediated ATRP polymerization of styrene (St) at various reaction conditions. The catalyst efficiency was higher at feed ratio of St/UBP = 880 and 400 than ST/UBP = 200. The polymers were obtained with high molecular weight and narrow molecular weight distribution (Mw/Mn < 1.5). In the 1H and 13C NMR spectra of the polystyrene obtained with this catalyst system, the signals assignable to H2C=CH- group indicate the undecenyl chain-end structure of the polystyrene which confirmed that the ATRP of styrene was initiated by UBP. Finally, the H2C=HC- group of undecenyl chain end of the polystyrene was converted to epoxy group by oxidation reaction to yield a new epoxy end functional polystyrene. The 1H NMR spectrum of the polymer confirmed the quantitative conversion of H2C=CH- to epoxy group.